MEDIATING CIVIL DISPUTES THROUGH LOCAL WISDOM - Denny Suwondo (UNISSULA, 2020)
The purpose of the research is intended to bring people to prosperity, happiness, and harmony so that there is mediation with the value of local wisdom must be the basis of resolution in civil disputes. The approach used in this paper is a normative juridical approach. The findings in this study include that the law is for humans, not humans for the law, whose purpose is to bring people to prosperity, happiness, and harmony. So that there is mediation with the value of local wisdom must be the basis of resolution in civil disputes with due regard to referring to the win-win solution principle, what is meant by the disputing parties feel that no one is defeated, Achieve the inner glory and inner peace of the parties, Reinforcement of family values and sense of belonging to the disputing parties.